Poly(anhydride-esters) Comprised Exclusively of Naturally Occurring Antimicrobials and EDTA: Antioxidant and Antibacterial Activities - Carbone-Howell, Ashley L. (American Chemical Society, 2014)
[Image: see text] Carvacrol, thymol, and eugenol are naturally occurring phenolic compounds known to possess antimicrobial activity against a range of bacteria, as well as antioxidant activity. Biodegradable poly(anhydride-esters) composed of an ethylenediaminetetraacetic acid (EDTA) backbone and antimicrobial pendant groups (i.e., carvacrol, thymol, or eugenol) were synthesized via solution polymerization. The resulting polymers were characterized to confirm their chemical composition and understand their thermal properties and molecular weight. In vitro release studies demonstrated that polymer hydrolytic degradation was complete after 16 days, resulting in the release of free antimicrobials and EDTA. Antioxidant and antibacterial assays determined that polymer release media exhibited bioactivity similar to that of free compound, demonstrating that polymer incorporation and subsequent release had no effect on activity. These polymers completely degrade into components that are biologically relevant and have the capability to promote preservation of consumer products in the food and personal care industries via antimicrobial and antioxidant pathways.